The effect of intellectual capital and strategic leadership on organizational citizenship behavior with the moderating role of employees' professional ethics - seyed reza mousavifard (مدیریت و چشم انداز آموزش)
Abstract The aim of the current research is to investigate the effect of intellectual capital and strategic leadership on organizational citizenship behavior with the moderating role of professional ethics of employees in the General Department of Education of Kermanshah province. The research is applicable in terms of purpose and causal in terms of descriptive-survey nature. The statistical population of the research was the employees of the General Department of Education of Kermanshah province, and the sample size was determined using the Cochran formula of 304 people. A simple random sampling method was chosen. The data collection method was field data collection, and the required tools were Bontis's (1998) intellectual capital, Lear's (2012) strategic leadership, Oregon and Kanowski's (1988) organizational citizenship behavior, and researcher-made professional ethics questionnaires. The method of data analysis was descriptive statistics and structural equation modeling using Spss26 and Amos24 software. The findings showed that intellectual capital has a significant and positive effect on organizational citizenship behavior by 66%. Strategic leadership predicted changes in organizational citizenship behavior by 46%, Also, the moderating role of professional ethics of employees between intellectual capital and strategic leadership with organizational citizenship behavior was confirmed, and the moderating rate of this variable was equal to 5% and 3.2%, respectively. The results showed that intellectual capital has a greater effect on organizational citizenship behavior than strategic leadership. Therefore, it is necessary to pay more attention to intellectual capital in order to improve organizational citizenship behavior in the organization. Extended abstract Introduction Organizational citizenship behavior is a unique, voluntary and extra-task behavior that is effective in increasing the efficient performance of the organization and is directly or indirectly organized by the organization's formal reward system (Baharond et al, 2018). Organizational citizenship behavior is an extra-task behavior that exists in the organization among employees, which makes organizational communication stronger in order to solve internal organizational problems. In other words, employees who have good citizenship behavior voluntarily try to solve organizational problems and challenges and reduce the amount of organizational anomalies. Therefore, intellectual capital and strategic leadership can be used to improve and upgrade this important organizational component. Organizations use various resources to grow and improve in the competitive arena and increase their value, because knowledge is considered the most important capital of the organization. As a result, intellectual capital is considered a main and important element in the management of organizations (Peralta et al, 2018). The intellectual capital of a company's employees combines knowledge, experience, intellectual property and information that can be used to create long-term value (Minoja & Romano, 2021). In addition to the many effects of intellectual capital, strategic leadership is of great importance in improving organizational citizenship behavior. Strategic leadership is conceptualized as the process of forming a vision for the future, rendering it to subordinates, stimulating and motivating followers, and participating in strategy-supportive exchanges with peers and subordinates (Malkawi et al, 2017). Despite the high effects of intellectual capital and strategic leadership in organizations, as well as organizational citizenship behavior, it can be said that the professional ethics of employees can be considered a moderating factor. Professional ethics is a set of rules that people must follow voluntarily and based on the call of their conscience and nature in doing professional work; without having an external requirement, or suffer legal punishments in case of violation (Jeong et al, 2017). In line with the stated content, it can be said that the abcense or low level of professional ethics of employees can play a moderating role and reduce the effects of strategic leadership and intellectual capital, and on the other hand, the existence of professional ethics of employees with their clients and colleagues within the organization can improve organizational citizenship behavior. According to the stated contents, this research tries to answer the question: what is the extent of the effects of intellectual capital and strategic leadership on organizational citizenship behavior with the moderating role of professional ethics of employees in the General Department of Education of Kermanshah province? Theoretical Framework The term intellectual capital was first expressed by John Kenneth Galbraith (1969) (Bellucci et al, 2020). He not only mentions intellectual capital as a fixed asset, but also considers it an ideological process and a means to achieve a goal. Since 1982, the Organization for Economic Cooperation and Development has conducted many researches in the field of intellectual capital, and many researches have been conducted in European countries such as the Netherlands, Norway, Sweden, Denmark, Ireland, etc (Hemati & Mehrabi, 2011). Intellectual capital is generally divided into three dimensions: human capital, structural capital, and communication capital. Human capital is the most valuable asset of the organization, and the source of creativity and innovation. Human capital is considered a basic and primary part for the components of intellectual capital activities. Human capital includes knowledge, skills, experience and wisdom of people (Beattie & Smith, 2010). Strategic leadership is the ability to create a strategic vision for the organization and motivate others to accept that vision. Its most important characteristics are: 1) foresight, eloquence and stability; 2) commitment; 3) ability to receive information; 4) willingness to delegate authority and power; 5) political shrewdness" (Jaliliayn, 2021). The main goal of strategic leadership is the long-term survival of the organization in line with the main business goals. However, it also aims to achieve above-average profits at the same time. Therefore, the primary goal of strategic leadership is to gain profit (Tutar et al, 2011). Oregon et al (1988) used the term organizational citizenship behavior for the first time and defined it as follows: conscious and insightful individual behavior that is not directly and explicitly recognized by the formal reward system and generally improves the organization's functions. Researchers found that many factors influence organizational citizenship behavior; factors such as commitment, satisfaction, organizational justice, leadership style, personality traits, job characteristics and organizational characteristics (MohammadKhani et al, 2013). At first, the concept of professional ethics was used to mean work ethics and business ethics. Even today, some writers of professional ethics use the primary meaning of this concept to define it (Abbaspour & Hosseinzadeh, 2019). Professional ethics has many benefits for the organization from the internal aspect in terms of improving relations, improving the atmosphere of understanding and reducing conflicts, increasing the commitment and more employees and reducing costs due to control, and from the point of view of social responsibility, affects moral commitment in Paying attention to the importance of stakeholders, profitability increase, and competitive advantage by increasing the legitimacy of the organization and its actions (Chokprajakchat & Sumretphol, 2017). Methodology The current research is applicable in terms of purpose, and causal type of descriptive-survey in terms of nature. The type of data is quantitative and the required tool is a questionnaire. The method of collecting information is library-type, and the required tool is to scan books, articles and theses. The statistical population of the research is the employees of the General Department of Education of Kermanshah province. The size of the population is 1450 people; from which, by using Cochran's formula, 304 people were selected as a sample. The sampling method is simple due to the lack of access to the entire random statistical population. The data collection method was field data collection, and the required tools are questionnaires of intellectual capital of Bontis (1998), strategic leadership of Lear (2012), organizational citizenship behavior of Organ & Kanoski (1988), and researcher-made professional ethics. The data analysis method is descriptive statistics (mean and standard deviation) and structural equation modeling. The test to check the normality of the data is Kolmogorov-Smirnov. The software used is Spss26 and Amos24. Discussion and Results